2019
DOI: 10.3389/fneur.2019.00397
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Dysbiosis Index (SDI) in Gut Microbiome Are Associated With Brain Injury and Prognosis of Stroke

Abstract: Background: Significant dysbiosis occurs in the gut microbiome of stroke patients. Condensing these broad, complex changes into one index would greatly facilitate the clinical usage of gut microbiome data. Here, we formulated a gut microbiota index in patients with acute ischemic stroke based on their gut microbiota dysbiosis patterns and tested whether the index was correlated with brain injury and early outcome. Methods: A total of 104 patients with acute ischemic stroke an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
186
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 159 publications
(199 citation statements)
references
References 53 publications
(70 reference statements)
11
186
1
1
Order By: Relevance
“…It has been reported that gut microbiota composition may have an impact on stroke outcome. Our previous work showed that dysbiosis of the gut microbiota is correlated with a worsened stroke outcome in patients [20]. Similar ndings have been observed in mice.…”
Section: Introductionsupporting
confidence: 83%
“…It has been reported that gut microbiota composition may have an impact on stroke outcome. Our previous work showed that dysbiosis of the gut microbiota is correlated with a worsened stroke outcome in patients [20]. Similar ndings have been observed in mice.…”
Section: Introductionsupporting
confidence: 83%
“…Antibiotics may have played a role as mortality in the FMT-group was similar to the antibiotic treated-stroke group (Winek et al, 2016). Two other studies found more functional impairment, larger cerebral infarct volume, and increased intestinal, systemic and cerebral inflammation in (pseudo-)GF stroke mice that had received dysbiotic post-stroke mouse or human microbiota compared to mice receiving normal microbiota (Singh et al, 2016;Xia et al, 2019). In addition, gavage with normal microbiota led to reduced infarct volumes (Singh et al, 2016).…”
Section: Role Of the Gut Microbiota In Disease Symptoms And Pathogenesismentioning
confidence: 93%
“…In this study, there were significant differences in terms of NIHSS score, stroke recurrence, Hcy, LA, and brain atrophy between the PSCI and PSNCI groups, and we also observed the associations of these risk factors with GM. Previous studies have revealed that the incidence of post-event dementia was positively correlated with stroke severity (Pendlebury et al, 2019), and GM dysbiosis was positively correlated with NIHSS scores in stroke patients (Xia et al, 2019). Besides, stroke recurrence was a significant contributor to cognitive impairment through its association with white matter hyperintensities (WMH) (Georgakis et al, 2019).…”
Section: Figure 3 |mentioning
confidence: 99%